2005
DOI: 10.1093/toxsci/kfi336
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Signaling Mechanisms of Acetaminophen-Induced Liver Cell Death

Abstract: Acetaminophen hepatotoxicity is the leading cause of drug-induced liver failure. Despite substantial efforts in the past, the mechanisms of acetaminophen-induced liver cell injury are still incompletely understood. Recent advances suggest that reactive metabolite formation, glutathione depletion, and alkylation of proteins, especially mitochondrial proteins, are critical initiating events for the toxicity. Bcl-2 family members Bax and Bid then form pores in the outer mitochondrial membrane and release intermem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
376
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(401 citation statements)
references
References 109 publications
18
376
0
7
Order By: Relevance
“…Acetaminophen is a hepatic prooxidant that depletes glutathione. 43 Therefore, synergy between acetaminophen and CIH could be a result of diminished antioxidant defense. Thus, CIH may predispose to fulminant hepatocellular injury in the presence of the second insult.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen is a hepatic prooxidant that depletes glutathione. 43 Therefore, synergy between acetaminophen and CIH could be a result of diminished antioxidant defense. Thus, CIH may predispose to fulminant hepatocellular injury in the presence of the second insult.…”
Section: Discussionmentioning
confidence: 99%
“…4). Oxidant stress of mitochondria triggers the mitochondrial membrane permeability transition pore, loss of the membrane potential of the mitochondria, depletion of ATP, and release of intermembrane proteins that are responsible for the typical nuclear DNA fragmentation of APAP-induced cell death [67]. We have found that antioxidants, such as silymarin [68], protect the liver of rats intoxicated with APAP [69].…”
Section: Paracetamol-induced Liver Damage and Free Radicalsmentioning
confidence: 99%
“…In the past, researchers studying the toxic action mechanism of APAP focused on metabolic activation of the drug, depletion of glutathione, and covalent binding of the reactive metabolite N-acetyl-p-benzoquinone imine (NAPQI) to cellular proteins as the main cause of hepatic cell death [66]. More recently, it was discovered that covalent binding is not sufficient to kill liver cells but is a signal for the toxicity that requires amplification in the cell [67]. Intracellular steps critical for cell death include mitochondrial dysfunction and, importantly, the formation of ROS and peroxynitrite (Fig.…”
Section: Paracetamol-induced Liver Damage and Free Radicalsmentioning
confidence: 99%
“…Kon et al (15) found that mobilization of chelatable iron from lysosomes was key in acetaminophen hepatotoxicity. The formation of reactive oxygen species (ROS) increases following acetaminophen exposure, and agents that augment antioxidant defenses and scavenge ROS protect against acetaminophen toxicity in vitro and in vivo (16). In the present study, the mechanism and effect of Schisandra chinensis on acetaminophen-induced hepatotoxicity and liver failure in mice was evaluated by observing the extent of lysosomal disruption and ROS release.…”
Section: Introductionmentioning
confidence: 95%